Feedback from the EBF – Focus Workshop: bringing assay validation and analysis of biomarkers into practice. (May 2017) - Timmerman, Philip; Scheel Fjording, Marianne; Allinson, John; Arfvidsson, Cecilia; Barroso, Begoña; Diczfalusy, Ulf; Freeman, Adrian; Hickford, Elizabeth; Kandousi, Hamza; Katugampola, Sidath; Kunz, Ulrich; Nelson, Robert; et al.
European Bioanalysis Forum Focus Workshop, Lisbon, Portugal, 9–10 June 2016 At the recent European Bioanalysis Forum's Focus Workshop 'Bringing Assay Validation and Analysis of Biomarkers into Practice', the discussion on best practice for biomarker assay validation continued. Both the presentations and the adjacent panel discussions yielded valuable food for thought for the broader bioanalytical community. The present conference report summarizes the essence from these discussions and from the proposals or conclusions made by all delegates on how to increase the necessary connectivity of the stakeholders involved in the bioanalysis of biomarkers.